PELATIHAN PELAYANAN PRIMA UNTUK KARYAWAN DI MOMOO JUICE BAR & CAFFEE HARBOUR BAY KOTA BATAM - Syafruddin Rais; Rezki Alhamdi; Tito Pratama; Natal Olotua Sipayung; Taufik Bachrul Ulum Lubis; Dailami (JURNAL KEKER WISATA, 2024)
This research aims to explore the factors that influence excellent service in the context of the Caffee industry, with a focus on customer experience at Momoo Juice Bar & Caffeé Harbor Bay, Batam City. The research method used was a combination of a survey of several Caffee guests and in-depth interviews with customer service managers. The research results show that aspects of employee involvement, speed of response to customer requests, and quality of interaction have a significant impact on the level of guest satisfaction. Additionally, the findings highlight the importance of ongoing employee training to maintain high standards of service excellence. The implication of this research is the need for Momoo Juice Bar & Caffeé Harbor Bay, Batam City and perhaps also other cafes in the same industry to focus on developing employee interpersonal skills, using technology to increase response to customer requests, and increasing interdepartmental coordination to ensure a positive experience. seamless guest. This research contributes to the understanding of the importance of excellent service in the hotel industry and provides practical guidance for managers in improving the quality of service provided to guests.